Double staining glycohistochemical analysis of tumour associated glycoconjugates in Human mammary carcinoma - PRATHAP.P,; JAGANNATHAN.N,; SUKUMARAN.N, (International Journal of Pharma and Bio Sciences, 2016)
One of the most common cancer death in the world id due to Cancer of the Breast. It should be noted breast cancer can occur irrespective of sex, but predominantly in women. In order to demonstrate the expression of cancer associated carbohydrate antigens representing the first steps in glycosylation, different glyco histochemical methods viz. Carbohydrate staining were employed in addition to the conventional Haematoxylin and Eosin staining, to recognize the relation of the glycocalyx in infiltrating mammary adenocarcinoma tissue. Glycoconjugates are macromolecules generally carbohydrates with a protein/lipid component. Double staining glycohistochemical analysis of tumour associated glycoconjugates in human mammary carcinoma was performed based on the above methods to highlight the expression of the glycans or glycoconjugates, different staining techniques were employed on infiltrating ductal adenocarcinoma section of the breast. A total nine cases of infiltration ductal carcinoma cases were studied. This study reveals the localization of various tumor glycoconjugates the aberrant structures in most of the different mammary cancer tissues using PAS staining and Alcan Blue- PAS staining.